To complete the square for the quadratic equation \( y = -x^2 + 8x + 7 \), we will follow these steps:
-
Factor out the coefficient of \( x^2 \) (which is \(-1\) in this case) from the first two terms:
\[ y = - (x^2 - 8x) + 7 \]
-
Complete the square inside the parentheses. To do this, we take the coefficient of \( x \) (which is \(-8\)), divide it by 2 to get \(-4\), and square it to get \(16\). We then add and subtract this value inside the parentheses:
\[ y = - \left( x^2 - 8x + 16 - 16 \right) + 7 \]
Simplifying this, we have:
\[ y = - \left( (x - 4)^2 - 16 \right) + 7 \]
-
Distribute the negative sign:
\[ y = - (x - 4)^2 + 16 + 7 \]
Combine like terms:
\[ y = - (x - 4)^2 + 23 \]
Now, the function is in the vertex form \( y = a(x - h)^2 + k \), where \( (h, k) \) is the vertex. From our equation \( y = - (x - 4)^2 + 23 \), we can identify:
- The vertex \( (h, k) = (4, 23) \).
- The axis of symmetry is given by the line \( x = h \), which, in this case, is \( x = 4 \).
Summary
- Vertex: \( (4, 23) \)
- Axis of symmetry: \( x = 4 \)